Cover Jurnal Fitopatologi Vol. 20 No. 5, September 2024: Cover Jurnal Fitopatologi Vol. 20 No. 5, September 2024 - Editors Jurnal Fitopatologi Indonesia (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2024)
This editorial contains the front cover, editorial page, and back cover of the Jurnal Fitopatologi Vol. 20 No. 5, September 2024.